Adsorptive Removal of Atrazine From Contaminated Water Using Low-Cost Carbonaceous Materials: A Review - Ahmad, Munir; Riaz, Umair; Iqbal, Shazia; Ahmad, Jahangir; Rasheed, Hina; Al-Farraj, Abdullah S. F.; Al-Wabel, Mohammad I. (Frontiers in Materials, 2022)
chloro-4-ethylamino-6-isopropylamino-s-triazine) to eliminate undesirable weeds has resulted in elevated levelsthe accumulation of atrazine and its metabolites (diaminochlorotriazine, deisopropylatrazine, desethylatrazine, and atrazine mercapturate) in surface and groundwater around the worldabove maximum permissible limits (drinking water: 3 μg L−1 in USA, 0.1 μg L−1 in Europe, and 3.0 μg L−1 by WHO). Atrazine exhibited no to low degradation in aquatic environments; however, poor degradation in soil yields toxic metabolites, which serve as sink for groundwater resources. Due to mobility, atrazine and its metabolites can persist in various environmental matrices for decades without degradation, posing a serious threat to ecosystem sustainability and thus be removed from water resources. Majority of conventional wastewater treatment technologies are either expensive or inefficient. The carbonaceous materials such as activated carbon, biochar, carbon nanotubes, and graphene are consideredhave been employed as potent adsorbents for the efficient removal of atrazine along with its metabolites from wastewater. Thus, the efficacy of aforementioned carbonaceous adsorbents for atrazine removal has been discussed in this article by literature surveyreviewing of 160 published papers. Literature survey demonstrated the highest atrazine adsorption capacity of activated carbons (13.95–712.10 mg g-1), followed by biochar (4.55–409.84 mg g-1), and carbon nanotubes (28.21–110.80 mg g-1). Further, the major mechanisms controlling the atrazine removal through the carbonaceous adsorbents has been provided. Literature showed that aAtrazine adsorption onto the carbonaceous adsorbents was is a complex process involving single or multiple mechanisms, such as hydrogen–bonding, electrostatic-interactions, van der Waals forces, hydrophobic-interactions, pore-filling, and π-π electron-donor acceptor interactions, pore-filling, and partitioning. It is recommended that monitoring of atrazine and its metabolites in water resources, and their impacts on human and animal lives should be explored. Further, modification of carbon-based adsorbents with chemical, mechanical, and thermal means, as well as development of hybrid systems, may completely remove the prevailing atrazine and its metabolites from world water resources.